Community Service Learning Project, Department of Electrical and Computer Engineering, Faculty of Engineering, The University of the West Indies, St. Augustine [PowerPoint] - Romeo-Joseph, Juliet (My University, 2015)
This presentation defines "Community Service Learning" (CSL), identifies the best practice principles for higher education that relate to teaching and learning, and examines how CSL relates to the development of the student from a pedagogical standpoint and satisfies the mandate of The University of the West Indies (UWI) and its impact on the nation/region. It then presents a case study of the Community Service Learning Project, showing how it has been incorporated into the B.Sc. in Electrical and Computer Engineering programme, and identifies the overall project goals, logistics, outcomes, lessons learned, and future plans.
Contribution to the Panel on Showcasing Evidence of Good and Promising Practices at the Regional Conference on Institutionalising Best Practice in Higher Education, UWI, St. Augustine, Trinidad and Tobago, 24-26 June, 2015.
Keywords: Community Service Learning Project; Department of Electrical and Computer Engineering, UWI, St. Augustine; Best practices; Case studies; The University of the West Indies, St. Augustine; Higher education; Service learning